2019
DOI: 10.3389/fimmu.2019.00944
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase Kinase Is a Metabolic Checkpoint for Polarization of Macrophages to the M1 Phenotype

Abstract: Metabolic reprogramming during macrophage polarization supports the effector functions of these cells in health and disease. Here, we demonstrate that pyruvate dehydrogenase kinase (PDK), which inhibits the pyruvate dehydrogenase-mediated conversion of cytosolic pyruvate to mitochondrial acetyl-CoA, functions as a metabolic checkpoint in M1 macrophages. Polarization was not prevented by PDK2 or PDK4 deletion but was fully prevented by the combined deletion of PDK2 and PDK4; this lack of polarization was correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 28 publications
3
59
0
Order By: Relevance
“…Knockdown of PDK1 in murine BMDMs suppressed M1 by attenuating glycolytic flux, the expression of pro.inflammatory cytokines (TNF-α and IL-6) and consequently aerobic glycolysis, but enhanced M2 activation by mitochondrial respiration [220]. Moreover, combined deletion of two forms of pyruvate dehydrogenase kinase PDK2 and PDK4 in myeloid cells prevents M1 polarization and correlates with the improved mitochondrial respiration in mouse models [221]. Similarly, PDK1 was identified as a HIF-1α target gene, and HIF-1α-PDK1 axis induced active glycolysis with up-regulation of glycolytic genes, such as GLUT1, phosphoglycerate kinase 1 (PGK1) or lactate dehydrogenase A (LDHA) [222].…”
Section: The Key Metabolic Features Of M1 Macrophagesmentioning
confidence: 99%
“…Knockdown of PDK1 in murine BMDMs suppressed M1 by attenuating glycolytic flux, the expression of pro.inflammatory cytokines (TNF-α and IL-6) and consequently aerobic glycolysis, but enhanced M2 activation by mitochondrial respiration [220]. Moreover, combined deletion of two forms of pyruvate dehydrogenase kinase PDK2 and PDK4 in myeloid cells prevents M1 polarization and correlates with the improved mitochondrial respiration in mouse models [221]. Similarly, PDK1 was identified as a HIF-1α target gene, and HIF-1α-PDK1 axis induced active glycolysis with up-regulation of glycolytic genes, such as GLUT1, phosphoglycerate kinase 1 (PGK1) or lactate dehydrogenase A (LDHA) [222].…”
Section: The Key Metabolic Features Of M1 Macrophagesmentioning
confidence: 99%
“…Pyruvate dehydrogenase kinase (PDK) has been postulated to be important for M1 polarization as it reduces entry of carbons from glycolysis into the TCA cycle by inhibiting pyruvate dehydrogenase (PHD). Indeed, pharmacological inhibition of PDK2 and−4 blocks inflammatory activation of cultured macrophages (146). Myeloid-specific ablation of PDK2/4 using a bone-marrow transplant approach led to reduced weight gain, improved glucose tolerance and reduced adiposity and liver fat when fed a HFD.…”
Section: Tca Cyclementioning
confidence: 99%
“… 40 This immunometabolic disease mechanism was supported by a recent study, which demonstrated that both genetic and pharmacological inhibition of mitochondrial PDH kinase isozymes improves mitochondrial function and decreases expression of proinflammatory cytokines. 41 Taken together, our data suggest that fursultiamine disrupted metabolic reprogramming from OXPHOS to aerobic glycolysis, which could be associated with the attenuated inflammatory response in the RPE.…”
Section: Discussionmentioning
confidence: 55%